2022
DOI: 10.1007/s13555-022-00867-y
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Effectiveness and Drug Survival of Secukinumab in Vietnamese Patients with Psoriasis: Results from a Retrospective ENHANCE Study

Abstract: Introduction: Psoriasis (PsO), an immune-mediated inflammatory skin disorder, has substantial negative impact on patients' quality of life. Secukinumab, an approved treatment for moderate-to-severe plaque PsO, has an established long-term efficacy and safety profile. This study aims to provide real-world evidence of long-term effectiveness and retention rate of secukinumab in Vietnamese patients with PsO. Methods: This retrospective, observational study collected medical records of adult patients with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Ixekizumab DS in our study appears to be higher than the one for of secukinumab and anti‐TNFalpha at 5 years, and similar to brodalumab at 2 years, reported in some real‐life studies 4,18–20 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Ixekizumab DS in our study appears to be higher than the one for of secukinumab and anti‐TNFalpha at 5 years, and similar to brodalumab at 2 years, reported in some real‐life studies 4,18–20 …”
Section: Discussionsupporting
confidence: 84%
“…4,17 Ixekizumab DS in our study appears to be higher than the one for of secukinumab and anti-TNFalpha at 5 years, and similar to brodalumab at 2 years, reported in some real-life studies. 4,[18][19][20] The limitation of the present study is inherent to the retrospective monocentric design and only observed case analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Summary drug survival curves in blue, separate studies in grey. A Secukinumab [ 24 26 , 33 , 34 , 39 41 , 44 , 46 , 48 , 50 , 51 , 53 , 62 , 64 , 68 , 70 , 72 , 74 , 80 85 ], B ixekizumab [ 23 , 32 , 33 , 39 , 40 , 42 44 , 46 , 49 , 62 , 70 , 81 , 84 , 85 ], C brodalumab [ 39 , 40 , 58 , 62 , 84 87 ], D guselkumab [ 29 , 30 , 33 , 35 , 37 , 43 , 44 , 50 , 59 , 70 , 84 , 85 , 88 , 89 ], E risankizumab [ 27 , 50 , 84 , 85 , 90 ], ...…”
Section: Resultsmentioning
confidence: 99%